CreativeLab_Sci&Math - Cavadas, Bento (2019)
CreativeLab_Sci&Math is a project of the department of Mathematical and Natural Sciences of the Higher School of Education of Santarém that aims the innovation of the pedagogical practices in Higher Education. One main objective is the involvement of students in interdisciplinary activities that connects content and processes of knowledge construction of Mathematics and Physical-Natural Sciences. Those activities aim to develop competencies in students such as scientific, technical and technological knowledge, critical and creative thinking, reasoning and problem-solving skills. This process of curricular integration is based on a strong collaborative work among the teacher educators of both areas. This article presents the work dynamics, difficulties and benefits that this collaborative process has brought to students’ learning, our didactic practices and professional development, as well as future challenges.